Analisis Soal Uji Kompetensi Pada Buku Paket Matematika Siswa Kurikulum 2013 untuk SMP/MTs Kelas VII Semester 1 Ditinjau dari Taksonomi Bloom - Ni Nyoman Yulia Paicasari; Ketut Sarjana; Eka Kurniawan; Syahrul Azmi (Griya Journal of Mathematics Education and Application, 2021)
The purpose of this study was to identify the cognitive level of competency test questions in the mathematics textbook for students of 2013 Curriculum for SMP/MTs grade 7th semester 1 reviewed from Revised Bloom Taxonomy. Therefore, this type of research is descriptive research. The data source in this study is the student mathematics textbook 2013 Curriculum Edition 2017 Revision for SMP / MTs grade VII semester 1. While the research variable is the cognitive level of each item of competency test in the 2013 Curriculum student mathematics textbook for SMP/MTs grade 7th semester 1. Data collection was performed by using the documentation and questionnaire methods. The guideline used in the item analysis is the Revised Bloom Taxonomy cognitive level which includes C1-remembering; C2-understand; C3-applying; C4-analyze; C5-evaluate; and C6-creating. The results of this study obtained the percentage of C1 cognitive level of 13.69%; C2 of 23.17%; C3 at 51.57%; C4 of 8.42%; C5 at 1.05% and C6 at 2.11%. It can be concluded that the results of the cognitive level of competency test questions in the mathematics textbook for students of Curriculum 2013 for SMP/MTs grade 7th semester 1 are still low and have not met the balance of the difficulty level of the questions.